Analisis Potensi Pengembangan Ekowisata Mangrove di Desa Maitara Tengah Kota Tidore Kepulauan - Novlandi Maradjabessy; Nuraini Adung Damsiki; Muhammad Ali Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to calculate the thickness and density of mangrove ecosystems in the waters of Maitara Tengah City of Tidore Islands and calculate the suitability of mangrove ecosystems for ecotourism in the waters of Maitara Tengah Village while the use of research is as reference material for further research activities as well as a basis for consideration in management of mangrove ecotourism areas using the concept of conservation for related agencies. The results of data collection at the two observation stations using the "line transect" method obtained the composition of mangrove species after being identified based on the characteristics of the shape of the roots, leaves, flowers and stem bark, so there were 2 types, namely Rhizophora apiculata, and Bruguiera gymnorhiza. The highest relative density value of mangrove species from the two stations was Rhizophora apiculata and the lowest relative density value was Bruguiera gymnorrhiza. The area suitability value for mangrove ecotourism obtained shows that Maitara Tengah Village is feasible to be used as a mangrove ecotourism area